The IKZF1 N159S mutation is associated with poor outcome and a distinct molecular profile in adult patients with AML - Stasik, Sebastian; Eckardt, Jan-Niklas; Röllig, Christoph; Baldus, Claudia; Platzbecker, Uwe; Serve, Hubert; Müller-Tidow, Carsten; Schäfer-Eckart, Kerstin; Kaufmann, Martin; Krause, Stefan W.; Sauer, Tim; Hänel, Mathias; et al. (British journal of haematology, 2025)
IKZF1 mutations are recurrent alterations in acute myeloid leukaemia (AML), and hotspot point mutation, N159S, has recently been associated with unique gene expression and adverse risk. To better understand the molecular and clinical associations of IKZF1 N159S-mutated AML, we performed a pooled analysis of 4136 AML patients. IKZF1 N159 mutations were found in 39 patients (0.94%) in a dominant clonal constellation, indicating early genetic events. N159S mutations were associated with aberrant karyotype, significantly higher rates of myelodysplasia-related gene mutations, ELN2022 adverse risk and a particularly poor outcome, supporting the classification of IKZF1 N159S-mutated AML as a rare molecular subtype with adverse prognosis.